From the history formation of the modern system koloronomeniv (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article examines the history of the formation of color names in Ukrainian and other Slavic languages; considered division of colors on the main and additional; described the words that represent the color directly and indirectly.
Keywords: koloronomen; hue; color; layer lexical; semantics